Tracking Public Interest in Psychoactive Substances: Insights from Google Trends Data - Aşut, Gonca (Addicta: The Turkish Journal on Addictions, 2025)
This study explores public interest in psychoactive substances in Türkiye using Google Trends, a digital epidemiology tool that tracks search behaviors. Search trends were analyzed for five commonly used substances—cannabis, heroin, cocaine, amphetamine, and ecstasy—across different provinces, time periods, and seasonal variations. Results indicate that cannabis had the highest relative search volume nationwide, with regional variations showing Hakkari leading for heroin, Antalya for cannabis, Istanbul for cocaine and ecstasy, and Samsun for amphetamine. Search interest peaked during spring and summer, possibly linked to tourism and festival seasons. Cannabis-related searches increased by approximately 30% over the study period. Frequently searched topics included drug detection, health risks, and substance use among celebrities. Google Trends is a valuable tool for monitoring real-time public interest; however, it has some limitations. These include the lack of absolute search numbers, potential algorithmic biases, and the inability to determine user intent. Despite these challenges, Google Trends offers a cost-effective tool for tracking emerging drug trends and informing public health policies. Future studies should integrate Google Trends data with epidemiological records to improve surveillance and prevention strategies for substance use in Türkiye.